Africa speaks - Santana, Carlos 1947- (Concord Records Group, Inc., 2019)
The energy-infused, full-length album from Santana features the soulful vocals of Afro-Latin singer Buika. Santana and his eight-piece band convened at producer Rick Rubin's Shangri La Studios in Malibu, and in a ten-day period, they recorded an astonishing number of tracks, many of them in one take. Inspired by the melodies, sounds, and rhythms of Africa, Santana has created a truly memorable and powerful experience that also promises to be one of his most groundbreaking albums yet
Title from disc label
Songs co-written by Carlos Santana
Lyrics in booklet inserted in container
Keywords: Rock music / 2011-2020; World beat (Music); Latin jazz; Jazz-rock (Music); Rock music; 2011-2020; CD